FUZZY SOFT SET AND ITS APPLICATION IN SELECTING BEST CANDIDATE(S) FOR A JOB USING AGGREGATE FUZZY SET APPROACH - Balami, H. M.; Onyeozili, I. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Molodtsov in 1999 introduced the concept of soft set theory as a general mathematical tool for handling uncertainties about vague concepts. In this paper, we recalled the definitions of soft set, fuzzy set and some basic operations in soft set. We presented the definition of fuzzy soft set and contributed some related algebraic properties with illustrative examples. We also defined extended intersection, restricted union, AND product, OR product and proved that associative laws holds with respect to AND and OR products. De Morgan’s laws and inclusions were stated and proved in the background of fuzzy soft set with respect to various operations with some relevant examples. Finally, we presented the application of fuzzy soft set in multicriteria decision making in choosing a best candidate for a job using aggregate fuzzy set technique.2010 AMS Classification: 03E70, 03E04.